Effectiveness of Spinal Stabilization Exercises with Functional Belts on Non-Specific Lower Back Pain and Pain-Related Functional Conditions in Basketball Players - Paulius Paškevičius; Vilma Dudonienė (Lithuanian Sports University, 2020)
Background. According to various researchers, lower back pain is experienced by 60-85% of population at least once in a lifetime and up to 94 % in athletes, in addition, back pain is the most common complaint of basketball players. Spinal stabilization exercises, performed in different ways, are most often used in the prevention of sports-related injuries in athletes, but still it remains unclear which is the most effective one. Aim of the study. To determine the effect of different stabilization programs on non-specific lower back pain and functional status of basketball players. Methods. The study was performed with the voluntary consent of subjects. It included 40 subjects who were divided into two groups: first, basketball players (n = 20) who performed spinal stabilization exercises on the mat, and second, basketball players (n = 20) who performed spinal stabilization exercises with functional belts. Subjects' back pain was assessed on a pain analogy scale (SAS), pain-related function was assessed using the Oswestry Disability Questionnaire, static endurance of basketball players' trunk muscles was assessed using S. McGill's tests, and spinal mobility was assessed using the Schober test. All of the measurements were taken pre and post different interventions. Results. A spinal stabilization exercise program without functional belts reduced (p < 0.05) lower back pain and improved (p < 0.05) the functional condition of basketball players. A spinal stabilization exercise program with functional belts reduced (p < 0.05) lower back pain and improved (p < 0.05) functional status. No statistically significant differences were found between the effectiveness of the two stabilization programs used. Conclusion. Spinal stabilization exercises with functional belts and traditional spinal stabilization exercises can be used to reduce back pain, pain-related functional disability in basketball players; however, for greater spinal mobility, it is better to choose exercises with functional belts, and aiming to increase static endurance of trunk muscles it is advisable to use traditional stabilization exercises. Keywords: basketball players, back pain, spinal stability, functional belts.